(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Being able to evaluate risks is an important task in many areas of human activity: economics, ecology, etc. In case of a sufficient amount of source information the risk is evaluated using statistical methods. However, in reality the sufficiency of statistical data in risk assessment is more exceptional than normal. In such cases experts’ assessment make the only source of data. Experts are able to provide the necessary for analysis data due to their professional knowledge and experience. Certain amount of factors, which is to be evaluated by an expert (experts), significantly affects the process of experts’ assessment. If a big number of relevant factors occur, an expert may face a problem of defining links between “factors” and “outcome”. Fuzzy multiple criteria decision making approach can be used to solve the problem. Ecological risk assessment towards human health in case of gaseous substances escape at a chemical factory using hierarchical method and fuzzy multiple criteria decision making approach has been analyzed in the article.